The Islamic Revolution of Iran seen by Michel Foucault : “Political Spirituality” and Revolutionary Metaphysics in Shiite Islam - Vittor, Luis Alberto (2019)
Fil: Fil: Vittor, Luis Alberto. Universidad Nacional de Rosario. Centro de Estudios Árabes e Islámicos Doctor Osvaldo Machado Mouret; Argentina.